Poor deer : a novel - Oshetsky, Claire (Ecco, an imprint of HarperCollinsPublishers, 2024)
"Margaret Murphy is a weaver of fantastic tales, growing up in a world where the truth is too much for one little girl to endure. Her first memory is of the day her friend Agnes died. No one blames Margaret. Not in so many words. Her mother insists to everyone who will listen that her daughter never even left the house that day. Left alone to make sense of tragedy, Margaret wills herself to forget these unbearable memories, replacing them with imagined stories full of faith and magic--that always end happily. Enter Poor Deer: a strange and formidable creature who winds her way uninvited into Margaret's made-up tales. Poor Deer will not rest until Margaret faces the truth about her past and atones for her role in Agnes's death." -- Dust jacket.